International mobility of the highly skilled: Brain gain, brain drain or brain exchange - Thomas Straubhaar (Hamburg Institute of International Economics (HWWA), 2000)
The aim of this paper was to shift the focus from a negative prejudice about immigration towards a much more positive evaluation. More and more the migration pattern changes from a blue-collar migration of low qualified workers towards a whitecollar mobility of highly skilled professionals. It has to be stressed strongly that - strikingly enough - most migrants are relatively well qualified. Just to mention a new IMF study (Carrington/Detragiache 1999:47), the US data show that immigration flows of individuals with no more than a primary education are quite small, and reach only about 500?000 individuals out of a total of 7 million immigrants! ,,For most countries, people with a tertiary education have the highest migration rate ... Thus, migrant to the Unites States tend to be better educated than the average person in their home (that is the sending) country, and the proportion of very highly educated people who migrate is particularly high“ (Carrington/Detragiache 1999:48). So, these data clearly indicate that there is a substantial brain drain. Another question of quite similar importance is, why the US only should get a brain gain. Why not the EU? The immigration of highly skilled is crucial and decisive for growth and wealth of nations in the 21st century. Once again this is clearly seen and strategically developed in the US. The USA attracts highly skilled people from all over the world because of a number of natural as well as artificial benefits (,,sun, sea, and sand“, close relations between industry and universities etc.) and, therefore, experiences a ,,Brain Gain“ that stimulates growth. In the case of Europe, mobility is mainly intra-European, representing a ,,Brain Exchange“. This is being fuelled by the Europeanisation of production and the creation of an internal labour market. However, the EU lacks the magnetic power to attract high skilled foreign scientists and to become leading centres of research intensive (service) production. For Eastern Europe there is a fear of a ,,Brain Drain“ that will not be directed towards the EU but rather towards the US.
Keywords: 330; Brain Drain; Hochqualifizierte Arbeitskräfte; Internationale Arbeitsmobilität; Migrationspolitik; Bildungsinvestition; Neue Wachstumstheorie; Theorie; Welt; EU-Staaten